2005
DOI: 10.1029/2004wr003690
|View full text |Cite
|
Sign up to set email alerts
|

PSEM_2D: A physically based model of erosion processes at the plot scale

Abstract: [1] This paper presents the development and first applications of the Plot Soil Erosion Model 2D (PSEM_2D). Infiltration is computed using a Green and Ampt model, overland flow is computed using the depth-averaged two-dimensional unsteady flow equations (Saint Venant equations), and soil erosion is computed by combining the equation of mass conservation of sediment and a detachment-transport coupling model for erosion by runoff. A shear stress approach is used to determine the transport capacity. The formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 27 publications
1
61
0
1
Order By: Relevance
“…From equation (32), a and a d are flow depthdependent soil detachability coefficients for the original soil and deposited layer (with threshold values denoted by the subscript 0), respectively, h is the threshold depth for the detachment rates, is a soil characteristic parameter, p i (0 < p i 1 and AEp i ¼ 1) is the proportion of sediment in size class i of the original uneroded soil, H (0 H 1) is the protection factor provided by the deposited layer, F r is the fraction of excess stream power effective in entrainment, J e is the specific energy of entrainment, is the water density, s is the particle solid density, g is the magnitude of gravitational acceleration, ¼ gS 0 q is the stream power with cr the critical threshold stream power below which r i and r di are zero, i is fall velocity, and m à is the mass per unit area of deposited sediment required to protect the original soil from further erosion. The HR concept of separating out the layer of deposited sediment has now been adopted in more recent models [Kinnell, 2005;Nord and Esteves, 2005].…”
Section: Sediment Transport In Overland Flow: the Hairsine-rose Modelmentioning
confidence: 99%
“…From equation (32), a and a d are flow depthdependent soil detachability coefficients for the original soil and deposited layer (with threshold values denoted by the subscript 0), respectively, h is the threshold depth for the detachment rates, is a soil characteristic parameter, p i (0 < p i 1 and AEp i ¼ 1) is the proportion of sediment in size class i of the original uneroded soil, H (0 H 1) is the protection factor provided by the deposited layer, F r is the fraction of excess stream power effective in entrainment, J e is the specific energy of entrainment, is the water density, s is the particle solid density, g is the magnitude of gravitational acceleration, ¼ gS 0 q is the stream power with cr the critical threshold stream power below which r i and r di are zero, i is fall velocity, and m à is the mass per unit area of deposited sediment required to protect the original soil from further erosion. The HR concept of separating out the layer of deposited sediment has now been adopted in more recent models [Kinnell, 2005;Nord and Esteves, 2005].…”
Section: Sediment Transport In Overland Flow: the Hairsine-rose Modelmentioning
confidence: 99%
“…PSEM 2D, Plot Soil-Erosion Model 2D (Nord and Esteves, 2005;Esteves et al, 2000b), is a soil-erosion model dedicated to small experimental plots, typically of less than 100 m². Overland flow is described by the depth-averaged two-dimensional unsteady flow equations commonly referred to as the Saint-Venant equations (Zhang and Cundy, 1989 where S fx is the friction slope in the x direction (m m -1 ), S fy is the friction slope in the y direction (m m -1 ) and u x and u y are the velocity components in the x and y directions, respectively (m s -1 ).…”
Section: The Modelsmentioning
confidence: 99%
“…Cerdan et al (2002), for example, reported 10 t ha -1 of rill and gully erosion in a single month in a 94-ha catchment in Normandy (France) during the dramatic winter of 1999, while water erosion in the region is normally dominated by interrill processes. However and despite these observations, the dynamics of rill patterns, and the onset of rilling, are not taken into account in most soil-erosion models, with the noticeable exception of experimental models, such as RillGrow (Favis-Mortlock, 1998) or novel models in their preliminary versions, such as PSEM_2D (Nord and Esteves, 2005) or MAHLERAN (Wainwright et al, in review). The WEPP model, described by Gilley et al (1988), for example, assumes the rill density is one rill per metre transversally to the slope.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies (e.g. Jetten et al 1999Jetten et al , 2003Tucker & Whipple 2002;Tucker 2004;Van Griensven et al 2006) applied sensitivity analysis on various erosion models such as MPSIAC (Behnam & Parehkar 2011), CREAM (Lane & Ferriera 1982), EUROSEM (Veihe & Quinton 2000), WEPP (Nearing et al 1990), PSEM-2D (Nord & Esteves 2005), USLE (Tattari & Bärlund 2001;Liu & Liu 2010), GUEST (Misra & Rose 1996), ANSWERS (De Roo et al 1989), etc. Furthermore, White and Chaubey (2005) used sensitivity analysis to identify the parameters that most influence predicted flow, sediment and nutrient outcomes for the Soil and Water Assessment Tool (SWAT) model.…”
mentioning
confidence: 99%